The Soviet Union and the Czechoslovak army, 1948-1983 : uncertain allegiance - Rice, Condoleezza, 1954- (Princeton University Press, 1984)
This study of the tensions of military clientage focuses on Czechoslovakia to explore the ambiguous position of the military forces of East European countries and to show how the military's dual role as instrument of both national defense and the Soviet-controlled socialist alliance" fundamentally affects the interaction of military and political elites in Eastern Europe. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Outgrowth of a dissertation completed at the Graduate School of International Studies, Denver University.
Keywords: Komunistická strana Československa -- History.; Komunistická strana Československa; Civil-military relations -- Czechoslovakia -- History -- 20th century.; Czechoslovakia -- Armed Forces -- History.; Soviet Union -- Military relations -- Czechoslovakia.; Czechoslovakia -- Military relations -- Soviet Union.; Relations pouvoir civil-pouvoir militaire -- Tchécoslovaquie -- Histoire -- 20e siècle.; HISTORY -- General.; POLITICAL SCIENCE -- Political Process -- Political Advocacy.; Armed Forces; Civil-military relations; Military relations; Czechoslovakia; Soviet Union; 1900-1999; History